Keratoplasties Surgical techniques and complications - Mosca, Luigi (IntechOpen, 2012)
In this book, the authors illustrate different therapeutic and surgical approaches to treating various corneal pathologies. This edition in electronic format allows universal access to everybody regardless of the time of day or setting, portability, and speed of information access. Such features show more feasibility for all readers and reduce the time necessary for research. This book will be a good tool for students as well as specialists working in the field of corneal transplantation, to improve their knowledge of treatment of corneal disease.